DESKRIPSI MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS VIII DI SMPN 1 BUKITTINGGI BERDASARKAN GENDER - Riski Sakinah Aprilia; Isnaniah Isnaniah; Elydar Elydar (Universitas Pahlawan Tuanku Tambusai, 2022)
This research discusses related to learning interest in grade VIII students of SMP 1 Bukittinggi in the 2022 school year. The purpose of this study is to describe the interest in learning mathematics in female students and male students in class VIII A of SMP 1 Bukittinggi. The method in this study is descriptive qualitative. The subjects of the study were 25 students of class VIII A and a class VIII mathematics teacher at SMP 1 Bukittinggi. Research data collection using questionnaires and interviews. The results of the study are as follows: classically, the data of the overall student learning interest questionnaire averaged a percentage of 59%. So, the conclusion is that most of the grade IV students of SDN 18 Tebing Tinggi have an interest in learning mathematics. Meanwhile, based on gender, it was found that the interest in learning mathematics in male students was higher than that of female students (61% > 57%). This is also in accordance with the results of an interview with the homeroom teacher of SDN 18 Tebing Tinggi who also stated that the interest in learning mathematics in male students is higher. Keywords: interest in learning, mathematics, gender